Chiral Squaramide‐Catalyzed Asymmetric Mannich Reactions for Synthesis of Fluorinated 3,3′‐Bisoxindoles - Li, Bing‐Yu; Du, Da‐Ming (Advanced synthesis & catalysis, 2018)
A squaramide‐catalyzed asymmetric Mannich reaction of 3‐fluorooxindoles to isatin‐derived imines for synthesis of fluorinated 3,3′‐bisoxindoles with two contiguous stereocenters under mild conditions was developed. The corresponding 3,3′‐bisoxindoles were obtained in excellent yields with excellent diastereo‐ and enantioselectivities (up to 99% yield, >99:1 dr and >99% ee). What's more, this reaction can be gram‐scaled without compromising yield and stereoselectivity.